2012
DOI: 10.5923/j.ijaf.20120201.18
|View full text |Cite
|
Sign up to set email alerts
|

Different Approaches of Bio-control Agents for Controlling Root Rot Incidence of Some Vegetables under Greenhouse Conditions

Abstract: Different approaches of some antagonistic fungal, bacterial and yeast agents applied as seed treatment or soil drench was evaluated against various soil-borne pathogens causing vegetables root rot disease under greenhouse conditions. The tested pathogenic fungi were Alternaria solani Fusarium solani, F. oxysporum, Rhizoctonia solani, Sclerotium rolfsii, Macrophomina phaseolina and Pythium sp., meanwhile the tested bio-agents were Trichoderma harzianum, T. Viride and Bacillus subtilis, Pseudomonas flourescens a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…In the natural environment, crop surfaces are frequently wetted by rainfall, dewfall, fog, or cloud mist. Therefore, the special hydrophobicity/hydrophilicity of BCA cells may contribute to better adhesion properties to the surface of crops and reduce the overall leaching of yeast cells (Abdel-Kader et al 2012; Krasowska and Sigler 2014).…”
Section: Resultsmentioning
confidence: 99%
“…In the natural environment, crop surfaces are frequently wetted by rainfall, dewfall, fog, or cloud mist. Therefore, the special hydrophobicity/hydrophilicity of BCA cells may contribute to better adhesion properties to the surface of crops and reduce the overall leaching of yeast cells (Abdel-Kader et al 2012; Krasowska and Sigler 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have shown that root drench treatment works better than foliar spray (Srivastava et al 2011). Soil drench of T. harzianum and T. viride was more effective than seed treatment in suppressing root rot of vegetables (Abdel-Kader et al 2012). Delivering Trichoderma elicitors through a combined application of different delivery systems will synergize the priming effect and thereby suppress the pathogenic propagules.…”
Section: Discussionmentioning
confidence: 99%
“…The experiment was arranged in a completely randomized design with four replicates, each replicate had five pots for each isolate and control treatment. Root rot disease incidence was estimated and calculated as percentage of pre-and post-emergence dampingoff after 15 and 30 days from sowing date, while survival pecent was after 30 days from sowing according to Abdel-Kader et al (2012).…”
Section: Pot Experimentsmentioning
confidence: 99%
“…Likely, treating seeds or foliage treatment of many crops with biocontrol agents such Trichoderma spp. was effective to suppress many pathogens (Abdel-Kader et al, 2012), protect pea and radish seedlings against pathogens attack as well as reducing the incidence of damping-off (Lifshitz et al, 1986). However, Ghanbarzadeh et al (2016) concluded that applying Trichoderma harzianum was less effective for wilt control than the chemical fungicides, but it highly improved growth and yield of onion plants.…”
Section: Introductionmentioning
confidence: 99%